Application of an Implementation Science Framework to Policies on Immediate Postpartum Long-Acting Reversible Contraception. (March 2019) - DeSisto, Carla L.; Kroelinger, Charlan D.; Estrich, Cameron; Velonis, Alisa; Uesugi, Keriann; Goodman, David A.; Pliska, Ellen; Akbarali, Sanaa; Rankin, Kristin M.
Objectives: Implementation science provides useful tools for guiding and evaluating the integration of evidence-based interventions with standard practice. The objective of our study was to demonstrate the usefulness of applying an implementation science framework—the Consolidated Framework for Implementation Research (CFIR)—to increase understanding of implementation of complex statewide public health initiatives, using the example of Medicaid immediate postpartum long-acting reversible contraception (LARC) policies. Methods: We conducted semistructured telephone interviews with the 13 state teams participating in the Immediate Postpartum LARC Learning Community. We asked teams to describe the implementation facilitators, barriers, and strategies in 8 focus areas of the Learning Community. We audio-recorded and transcribed interviews and then coded each interview according to the domains and constructs (ie, theoretical concepts) of the CFIR. Results: Cosmopolitanism (ie, networking with external organizations) was the most frequently coded construct of the framework. A related construct was networks and communications (ie, the nature and quality of social networks and formal and informal communications in an organization). Within the construct of cost, state teams identified barriers that were often unable to be overcome. Trialability (ie, ability to test the intervention on a small scale) and engaging champions (ie, attracting and involving persons who dedicate themselves to supporting the intervention in an organization) were among the most salient constructs of the framework and were the sources of many implementation strategies. Conclusions: State leaders and program staff members may benefit from considering the CFIR domains and constructs in the planning, implementation, and evaluation of complex statewide public health initiatives.